(Mis)quoting King: commemorative stewardship and ethos in the controversy over the Martin Luther King Jr. Memorial. (3rd April 2019) - VanderHaagen, Sara C.
Abstract: Prior to the unveiling of the Martin Luther King Jr. Memorial in Washington, D.C. in the fall of 2011, controversy swirled about a paraphrased quotation etched on the side of King's likeness. The paraphrase, which read, "I was a drum major for justice, peace, and righteousness, " was derived from a sermon given by King in 1968. This essay examines the quotation controversy, which first erupted in August 2011, just before the memorial's scheduled dedication. The debate over this "misquote" seems at first to be about historical accuracy—i.e. whether the paraphrase accurately reflects what King said and who he was. However, I argue that this debate actually reveals more about how elites use the discourse of "commemorative stewardship" to secure the credibility to speak on, make decisions about, and ultimately control interpretations of public memories. Participants' claims rely on a rhetoric of commemorative stewardship that acknowledges a public obligation, expresses a commitment to a sacred memory, emphasizes the best practices of shared responsibility and accountability, and demonstrates investment in the good of future generations. Tracing the rhetoric of stewardship in the debate shows how critics of the paraphrased inscription were able to achieve their goal of "correcting" the perceived error while deflecting attention from other controversial elements of the memorial.